All-normal-dispersion passively mode-locked Yb-doped fiber ring laser based on a graphene oxide saturable absorber - Li, X. H. (2013)
We have demonstrated an all-normal-dispersion passively mode-locked Yb-doped fiber laser using a graphene oxide/polyvinyl alcohol (GO–PVA) saturable absorber without surfactant, for the first time to the best of our knowledge. The experimental results show that the pulse duration of the mode-locked lasers varies from 191 ps to 1.68 ns, while the cavity round trip time changes from 24 to 458 ns, through the variation of the cavity length. In addition, the proposed passively mode-locked fiber laser demonstrates a maximum average output power of 539 mW with a laser cavity length of 94 m, and the corresponding single pulse energy reaches 0.429 μJ. The proposed mode-locked fiber lasers with large chirp pulses may find potential applications in fiber chirped pulse amplification systems for micromachining, material processing and diagnostic applications.